Hour Block Based Demand Response for Optimal Energy Trading Profits in Networked Microgrids - Vankudoth, Lokesh; Badar, Altaf Q. H. (Distributed Generation & Alternative Energy Journal, 2022)
Microgrids are a small-scale power system that integrates Distributed Generation, Energy Storage Systems and controllable loads. The intermittent and variable nature of renewable generation leads to a complex control mechanism required for Microgrids. Microgrids that are geographically close to each other are interconnected to form Networked Microgrids. Networked Microgrids provide enhanced benefits of resource sharing to Microgrids, thus, improving the reliability and operation costs while reducing the environmental impact. The Microgrids, based on their generation and load profiles, can perform energy trading within the Networked Microgrid system for achieving optimized operational costs. In this paper, the impact of a novel hour block-based demand response program in Networked Microgrids is explored. In the proposed model, hour blocks are formed in a Networked Microgrids environment, dependent on generation and load imbalance, the role of Microgrids and the Time-of-Use tariff system. The Particle Swarm Optimization method is used to optimize the individual and overall economic benefits of Microgrids in the Networked Microgrid system. The simulations of the proposed method are performed on a Networked Microgrid system having 4 Microgrids. The results show a credible reduction in costs of operation for all Microgrids and the system as a whole.